2020
DOI: 10.3390/en13236433
|View full text |Cite
|
Sign up to set email alerts
|

Fire Behavior of Electrical Installations in Buildings

Abstract: Electrical installations are a significant component of fire load inside a building, although they are often neglected in the overall fire safety analysis and are not subjected to any kind of fire safety evaluation of a building. A typical electrical installation unconnected to the mains was experimentally studied using a single burning item (SBI) test apparatus, fixed to two types of popular non-combustible or combustible (wooden-based) backgrounds simulating a typical building internal wall or ceiling. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A transformer fire is categorized as an electrical fire, and electrical equipment is an important part of the fire load in buildings [11]. Compared with an ordinary fire, it is more difficult to extinguish an electrical fire, since this requires a fire extinguishing medium with both high isolation performance and fire extinguishing efficiency [12].…”
Section: Introductionmentioning
confidence: 99%
“…A transformer fire is categorized as an electrical fire, and electrical equipment is an important part of the fire load in buildings [11]. Compared with an ordinary fire, it is more difficult to extinguish an electrical fire, since this requires a fire extinguishing medium with both high isolation performance and fire extinguishing efficiency [12].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the risk of fires through early warning is an important issue worthy of attention. [1][2][3][4] Polyvinyl chloride (PVC) is one of the most widely used cable insulation materials, which usually contains phthalates (PAEs), and is a widely used plasticizer to improve the flexibility and extensibility of plastic products. [1][2][3][4] Studies have shown that PVC cables at a heating temperature higher than 110 1C will release some gases that are not common in the environment, such as dioctyl phthalate (DOP).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of the wire used to connect the electric devices is also important. An excessive temperature of an operational conductor may cause insulation to become damaged and, consequently, it may lead to short-circuits between individual conductors of wires in a bundle [4].…”
Section: Introductionmentioning
confidence: 99%